Extraction and antibacterial evaluation of marine AMPs against diabetic wound pathogens - Deepak Tom Jose, C. Uma, P. Sivagurunathan, B. Aswini, M. D. Dinesh (Journal of Applied Pharmaceutical Science, 2020)
The need for an alternative wound dressing material with effective coatings using antimicrobial peptides (AMPs) from a marine fish (Carangoides malabaricus) was selected as the primary objective in the present research. The AMPs were extracted and purified using standard biochemical methods and the fractional concentrations were selected to coat nonadherent wound dressing materials. Antibacterial activity, drug release behavior, and biocompatibility of the developed dressing material were studied. As the antibacterial activity, drug releasing behavior, and biocompatible properties of the coated materials showed promising results, a novel tissue-engineered wound dressing material can be developed to meet the challenges in the medical industry in the near future. This application would act as a skin replacement or an equivalent material to treat diabetic foot ulcer cases caused by pyogenic bacterial species.
Keywords: Antimicrobial peptides, diabetic foot ulcer, pyogenic bacteria, wound healing, biocompatibility.